Study on the process of chloride invasion and deposition in concrete under dry-wet cycles and continuous loading. Issue 7 (October 2021) - Shen, Shiyi; Mei, Kaiyuan; Xue, Quan; Wang, Bin; Zhang, Liwei
Abstract: Concrete for marine construction is not only eroded by seawater but also affected by ocean tides. The corrosion of the concrete structure is severe in the tidal range zone and the splash zone under the frequent dry-wet cycles environment. In order to investigate the process of chloride invasion and deposition in concrete under continuous loading, this paper applied pre-loading to concrete samples and evaluated pore distribution, chloride ions invade, and deposition of chlorine salts in concrete samples under dry-wet cycles with the use of salt weighing method, X-ray diffraction (XRD) and micro-CT. The results showed that the chloride salt quickly invaded into the samples under the influence of dry-wet cycles. With dry-wet cycles, chlorine salt is deposited in the pores of the samples, and the amount of chloride salt deposition increased with time. The pre-applied stress loading condition inhibited the salt deposition process. The results of the XRD analysis showed that chloride ions combined with calcium ions and deposited in the cracks and pores of the concrete after penetrating into concrete.